(3NRGfI GdGOH hdH dHGH dSGf GdYQHs - (3YHO GdbGOQ Hf YeQ GdHZOGOj , J (B1093 (3g` s
(3ChdgG (B:s
(3GdTGgO GdNGeS hGdCQHYhf HYO GdeGFJjf aCfJ WdGb hGdWdGb CdjI KdGKG hef jNQb CMb hCXde s
(3BNQgG (B:s
(3hGdgLGf cQGe GdEHd hGdYhP LeY YGFP , hgj GdMOjKI hbO JbOe TQMg eaUdkG hGddg JYGdi CYde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B41s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs